Pengalaman Penyesuaian diri Mahasiswa Nonmuslim dalam Lingkungan Kampus Mayoritas Muslim: Studi Kualitatif (The Adjustment Experiences of Non-Muslim Students in a Muslim-Majority Campus Environment: A Qualitative Study) - Hanandhya, Mahira Imtinan; Nurriezqa, Aisyah Eldwina; Hidayat, Raisa Khaira; Marnila; Mubarok, Wildan; Sari, Kartika (Happiness: Journal of Psychology and Islamic Science, 2025)
Syiah Kuala University (USK) is one of the state universities in Indonesia located in Aceh, where the majority of students are Muslim. Such an environment can be an important factor that influences the experience of non-Muslim students in adjusting to an environment rich in Islamic values and norms. The purpose of this study is to determine how non-Muslim students at USK adjust, including the challenges they face and how they adapt to their surroundings. This study uses a qualitative method with a phenomenological approach. Data collection for this study was conducted through observation and in-depth interviews using a semi-structured interview model. There were five research participants obtained through purposive sampling, with the criteria being active students at USK who are non-Muslim. The results of this study show that the adjustment process of non-Muslim students is going quite well. Challenges in the form of cultural differences, religious activities, and social norms on campus were faced with an open attitude, mutual respect, respect for worship time, and adjusting the way of dressing. Conversely, the support of the environment greatly helped them to adapt. Peers, lecturers, and student organizations were perceived as tolerant. They felt mutual respect and received adjustments to their activity and worship schedules in accordance with their religion. The people around them also actively and openly build relationships with them, so that they feel accepted for who they are without discrimination.